Pengaruh Penggunaan Serbuk Cengkeh Sebagai Feed Additive Dalam Pakan Terhadap Pertumbuhan Dan Kelangsungan Hidup Benih Ikan Nila (Oreochromis niloticus) Strain Merah - Kiki Haetami; Luthfi Nur Aulia; Roffi Grandiosa Herman; Yuniar Mulyani (Jurnal Perikanan Unram, 2024)
Feed additives or feed additives are now starting to become a necessity as additional feed in fish feed that can increase fish growth. This research aims to determine the effect of using clove powder as a feed additive in feed on the growth rate and survival rate of red tilapia fingerlings. The research was carried out at the Aquaculture Laboratory Building 4, Faculty of Fisheries and Marine Sciences, Padjadjaran University, Jatinangor from June to August 2023. The research method used is an experimental method using a complete randomized design consisting of four treatments and four repeats. The treatment used is the use of clove powder at doses of 0% (control), 0.5%, 1%, and 1.5% as feed additives in commercial feed. The observation parameters consist of specific growth rate, survival rate, and water quality. The results showed that the use of clove powder as a feed additive in commercial feed with a dose of 0.5-1.5% tended to increase the growth rate of red tilapia fry with specific growth rate values ranging from 1.17 ± 0.30%/day - 1.27 ± 0.12%/day. The survival rate of red tilapia fry with a dose of clove powder use of 1.5% tended to give the best results (97.50 ± 5.00%). The water quality of red tilapia fry maintenance during the study met the requirements of water quality standards for tilapia farming